Atuação do psicólogo em contextos cirúrgicos: mapeamento bibliográfico em periódicos de psicologia no Brasil - Antoniassi, Raquel Pinheiro Niehues (2009)
The present work aims to make a bibliographic survey of the knowledge produced in the scientific literature of the Psychology in which it refers to the acting of a psychologist in surgical contexts. For so much, a metodological proceeding was proposed and tested for realization of bibliographic survey, whose stages allowed its structuring. A search in Brazilian journals of Psychology Qualis A and/or B, indexed on basis of virtual data BVS-Psi, for published articles from 2001 to 2008, with at least a psychologist as author and/or co-author was performed. Of a total of 7.550 published articles, there were selected 17 articles, which were paying attention to the established criteria of inclusion. For analysis, there were delimited categories of identification (author, place and chronology); of metodological and theoretic characteristics (theoretical approach, type of study and method); and of content (white type of surgery, population of the acting, proposed intervention and obtained results). It was noticed that the articles were published by psychologists (71,05 %), who are linked to postgraduate courses in institutions of superior teaching, especially USP (47,06 %). Empirical inquiries (76,48 %) were predominant, with cognitivecomportamental theoretical approach (41,18 %). There prevailed the use of semidirected interviews in the pre and/or post surgical period (23,54 %) with the objective to value feelings at pre and/or post surgical contexts (23,54 %) of the adult patient (47,06 %). There are proposed techniques of psychological intervention of evaluation (76,48 %) and pre-surgical preparation (52,95 %), aiming to prevent complications resulting from psychological factors. Because of the shortage of publications devoted specifically to the study of this form of acting, the necessity of new fronts of studies for a deep understanding of the means of acting of the psychologist in surgical contexts was discussed and proposed